Enhancing Foreign Language Learning through Educational Technology - Jerri Phua; Heru Wijayanto Aripradono (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Nowadays, the demand for foreign language learning has become a necessity due to globalization but traditional strategies are not free from problems. Educational technologies (EdTech), especially those powered by Artificial Intelligence (AI), augmented reality (AR) and/or virtual VR are following the trend and introducing new ways to enhance the efficiency of foreign language learning. Behavior and 2) This study examine the use of these technologies in foreign language learning through quality education. The study used descriptive qualitative methodology with a systematic review of related literature. The study results show that EdTech enables more interactive, personalized and integrated learning, which significantly enhances foreign language competency. However, there are known obstacles such as lack of infrastructure, inadequate teacher training and inaccessible areas. To overcome this, there is a need for E2E (EdTech to Ends) which aims to achieve maximum in foreign language education by using the power of EdTech.